Influencing Factors on Dynamic Capability and Operational Performance; The Case of Chongqing Cultural Industrial Parks - Song, Xiangqin; Khantanapha, Napaporn (วารสารนวัตกรรมการศึกษาและการวิจัย, 2026)
The development of China’s cultural industrial parks has played a significant role in promoting the growth of cultural industries and enhancing public engagement. This study aimed to (1) examine the factors influencing operational performance, (2) analyze the mediating role of dynamic capabilities between technical flexibility, structural flexibility, cultural flexibility, and operational performance in Chongqing Cultural Industrial Park, and (3) create a model to improve the operational performance of the Chongqing Cultural Industrial Park. The study employed mixed research methods, with the quantitative portion focusing on managers working in the Chongqing Cultural Industrial Park for over two years, with a sample size of 548 respondents. The qualitative aspect involved in-depth interviews with 10 key experts in the field of operational performance of cultural industrial parks. A convenience sampling method was used to select respondents, and data were collected using questionnaires and interview forms. Data analysis was conducted through descriptive statistics and Structural Equation Modeling (SEM) using AMOS software. The study found that: (1) Technical flexibility has a significant positive effect on park performance, while structural flexibility and cultural flexibility also significantly influence park performance; (2) Dynamic capabilities play a mediating role in the relationship between technical flexibility, structural flexibility, cultural flexibility, and operational performance in Chongqing Cultural Industrial Park; and (3) A model to improve operational performance in Chongqing Cultural Industrial Park suggests that enhancing technical flexibility, structural flexibility, and cultural flexibility not only directly improves operational performance but also boosts performance through the mediating role of dynamic capabilities. The study concludes that there are various approaches and theories available for improving the operational performance of industrial parks.